2017
DOI: 10.1101/lm.044784.116
|View full text |Cite
|
Sign up to set email alerts
|

Role of the anterior cingulate cortex in the retrieval of novel object recognition memory after a long delay

Abstract: Previous in vivo electrophysiological studies suggest that the anterior cingulate cortex (ACgx) is an important substrate of novel object recognition (NOR) memory. However, intervention studies are needed to confirm this conclusion and permanent lesion studies cannot distinguish effects on encoding and retrieval. The interval between encoding and retrieval tests may also be a critical determinant of the role of the ACgx. The current series of experiments used micro-infusion of the GABAA receptor agonist, musci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…The novel object recognition task is the ability to distinguish the novel from familiar stimuli which is directly dependent on the prefrontal cortex and hippocampus function ( Banks et al, 2012 ; Pezze et al, 2017 ). In Figure 3A , the data obtained analyzed using paired t -test exhibited that animals spent equal time to explore both object A1 and A2 and there were not any significant preference in exploring two objects in familiarization phase in the M/N-Day 1 [ t (6) = 0.7381, P = 0.4883; ns], Day 5 [ t (6) = 0.5558, P = 0.5984; ns] and Day 10 [ t (6) = 0.5176, P = 0.6109; ns] groups as compared with their respective Saline control groups (right panel).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel object recognition task is the ability to distinguish the novel from familiar stimuli which is directly dependent on the prefrontal cortex and hippocampus function ( Banks et al, 2012 ; Pezze et al, 2017 ). In Figure 3A , the data obtained analyzed using paired t -test exhibited that animals spent equal time to explore both object A1 and A2 and there were not any significant preference in exploring two objects in familiarization phase in the M/N-Day 1 [ t (6) = 0.7381, P = 0.4883; ns], Day 5 [ t (6) = 0.5558, P = 0.5984; ns] and Day 10 [ t (6) = 0.5176, P = 0.6109; ns] groups as compared with their respective Saline control groups (right panel).…”
Section: Resultsmentioning
confidence: 99%
“…The long-lasting impairment in learning or memory after acute or chronic opioid administration might be associated with the persistent impairment of different brain functions through several mechanisms, including changes in central signaling proteins ( Lou et al, 1999 ), activation of apoptosis signaling pathway ( Emeterio et al, 2006 ) or impaired synaptic plasticity ( Pu et al, 2002 ). Previous results suggest that the hippocampus and prefrontal cortex are involved in the NOR task ( Banks et al, 2012 ; Pezze et al, 2017 ). The current findings indicate impairment of short-term memory in the NOR task on days 3, 7, and 12 (timeline was shown in Figure 1 ) after methadone overdose.…”
Section: Discussionmentioning
confidence: 99%
“…We extended the analysis and found that NSPA-KO mice also have an impaired LTP in MPP-DG synapses of dorsal hippocampus and performed poorly in object recognition tests, while open field assays did not detect anxiety-like behaviors. Object recognition tests not only reflect dysfunction in the hippocampus, as the memory flexibility test, but also in other brain regions such as the amygdala and cingulate cortex [ 51 , 52 ], where NSPA is also expressed [ 18 , 20 ]. All these results highlight a role of NSPA in glutamatergic synaptic plasticity associated with memory processes in the hippocampus and suggest other functional alterations remaining to be defined at different brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…pointing the nose to the object at a distance of <1 cm and/or touching it with the nose (Leger et al, 2013;Okuda et al, 2004). Turning around, climbing or sitting on an object per se was not included in exploration times as the animals then often are not actively engaged in exploring the object but rather exhibit grooming behavior or are using the object to scan the environment (Bianchi et al, 2006;Leger et al, 2013;Li et al, 2011;Pezze et al, 2017;Roozendaal et al, 2006;Vogel-Ciernia & Wood, 2014;Wimmer et al, 2012). In order to analyze memory performance, a discrimination index was calculated as the difference in time exploring the novel and familiar object (or location), expressed as the ratio of the total time spent exploring both objects (i.e.…”
Section: Experimental Apparatus and Behavioral Proceduresmentioning
confidence: 99%